Comparative diagnostic performance of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) versus endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) for tissue sampling of solid pancreatic and non-pancreatic lesions without ROSE: a prospective multicenter study - Hussein Hassan Okasha; Mohammed Yousri Ahmed; Marwa A. Ahmed; Sameh Abou Elenin; Abeer Abdel-latif; Mahmoud Farouk; Mahmoud Gamal Ameen; Ahmed Hussein El-Habashi; Mahasen Akram Elshaer; Ahmed Elsayed Alzamzamy (SpringerOpen, 2024)
Abstract Background and aims Endoscopic ultrasound-guided tissue acquisition, including both fine-needle aspiration (EUS-FNA) and fine-needle biopsy (EUS-FNB), has been frequently performed to acquire samples from both pancreatic and non-pancreatic lesions. Still, the impact of the diagnostic yield between FNA and FNB is uncertain. We conducted this study to compare the diagnostic performance and accuracy of the 22-gauge FNA needles with the 22-gauge FNB needles in sampling solid pancreatic and non-pancreatic lesions. Methods This is a prospective multicenter study conducted on 465 cases presented with solid pancreatic or non-pancreatic lesions. Results Patients were 275 male and 190 females with a mean age of 59 years. Three-hundred twenty-seven patients had solid pancreatic lesions, while 138 had non-pancreatic lesions; 245 cases underwent EUS-FNA, and the remaining 211 cases underwent EUS-FNB. The presence of intact tissue core and sample adequacy was significantly higher in the FNB cases in solid pancreatic and non-pancreatic lesions. Blood contamination was significantly more in cell blocks and smears of EUS-FNA compared to that of EUS-FNB in solid pancreatic and non-pancreatic lesions. Based on histologic assessment of cell block only, EUS-FNB had more diagnostic accuracy (99%) than FNA (61%) (P-value < 0.005). However, cytological diagnosis by smears only showed no significant difference. The combined cytological and histological evaluation had 100% sensitivity, specificity, and accuracy. Conclusion EUS-FNA and EUS-FNB have comparable accuracy in diagnosing solid pancreatic and non-pancreatic lesions without ROSE. EUS-FNB is superior to EUS-FNA in acquiring intact tissue core and adequate samples with little blood contamination. Based on histological assessment (cell block/tissue core) only, EUS-FNA has less accuracy than EUS-FNB in diagnosing solid pancreatic lesions.